Lowland species of pentaphragma (pentaphragmataceae) in Peninsular Malaysia and Singapore - Kiew, Ruth (Malaysian Nature Society, 1989)
Pentaphragma horsfieldii is redefined to exclude var, flocculosum, which is transferred to P. ellipticum. P. ellipticum is reinstated to species level and its putative status as a hybrid between P. acuminatum and P. horsfieldii is denied. Keys to the Malayan taxa are provided.